PERAN PENYULUH AGAMA ISLAM DALAM MENCEGAH PERNIKAHAN USIA DINI DI DESA LUMPANGAN KECAMATAN PA’JUKUKANG KABUPATEN BANTAENG (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
This writing aims to determine the Role of Islamic Religious Instructors in Preventing Early Marriage in Lumpangan Village, Pa District, Bantaeng District Jukukang using this type of qualitative research. Data collection methods are observation, interview, and documentation. The results of this study indicate that the factors causing early-age marriage are: lack of socialization about Marriage Law No. 1 of 1974, economic factors, factors of promiscuity, and factors of education. Efforts to prevent early marriage and its impact, provide health education or commonly known as health socialization, through events such as majelis ta'lim and recitation. The implication of research in this research is that the extension workers should better understand the psychological condition of adolescents in order to make their approach easier in giving advice and enriching their knowledge of Islamic extension guidance so that when doing their counseling it is easier to apply the knowledge they get. Parents are expected to pay more attention to the condition of the psychological development of children and provide the love that is needed by children so that children do not seek pleasure.